Timeliness of financial reporting and corporate governance structure - Asri, Marsidi. (2005)
The issue of timeliness has been well recognized as one of the important attributes of financial reporting quality. Prior studies in this realm of research have only focused on the effects of firms' specific characteristics on reporting interval. To date, it can be said that there is no study which has directly attempted to gauge the influence of governance structure on the timely financial reporting of annual reports as far as the reseracher is concerned. The effects of poor corporate governance on financial reporting quality have been evidently reflected by the collapse of huge and well established companies like Parmalat, Enron etc. Due to the essential roles of corporate governance structure on the quality of financial reporting, the researcher is of the opinion that this study could present some new evidence to the extant of literature in both realms of research (i.e. the timeliness of financial reporting and corporate governance structure).